Reforms Implemented In The History Of Uzbekistan’s Development (Eurasian Journal of History, Geography and Economics, 2024)
This article is dedicated to a comprehensive study of the reforms implemented in the history of Uzbekistan’s development. It analyzes, in chronological order, the renewal processes that began after the country gained independence, as well as the reforms carried out in political, economic, social, and spiritual spheres. Special emphasis is placed on the distinctive aspects of the reforms implemented under the leadership of President Shavkat Mirziyoyev since 2016. The article also highlights the international recognition of the reforms carried out under President Mirziyoyev’s leadership, Uzbekistan’s development at a new stage, and future plans. It serves as an important theoretical and practical resource for researchers, historians, and those interested in the country’s developmental path and spiritual reforms. In President Mirziyoyev’s chronicle of activities, particular attention is paid to improving the system of state governance, fostering civil society, ensuring human rights and freedoms, and introducing new formats of interaction with the public